Positions of Différance - deconstruction as a strategy for reading the lifeworld (Phenomenology, Humanities and Sciences, 2023)
This theoretical essay aims to consider reading possibilities from the strategy of deconstruction inspired by Jacques Derrida’s thinking, constructing itself as a methodological foray and as intended to contribute to epistemological discussion about research on the phenomenon (or the Discourse) in Humanities. At first, clues are proposed for a Derridean reading of the phenomenon that, as such, demonstrates a textual structure. To this end, the essay starts from the centrality of the concept of Différance and how it circumscribes the possibility of an object for deconstructionist strategy analysis – i.e., the errancy of meaning, which simultaneously considers its dynamic and structure. In the following, this perspective of reading is defined as a strategy of analysis/reading of the lifeworld, showing how can contribute the concept of reality as a text to such discussion. Finally, a synthesis of the fundamental elements of this strategy is outlined. This essay concludes with the suggestion that the everyday lieworld is made up of a history of contingencies and crossings and of a verticality that, without committing to the idea of a last Arché, has a center that, however, is not identical to subjectivity, but is its producer – the very structure and dynamics of the Différance.
Keywords: Deconstruction; Différance; Epistemology; Lifeworld